E-Learning: Unpacking the Theories and Methodologies for Effective Digital Education - Ikromjon Esanboyvich Uzoqov; Boburmirzo Baxtiyar o‘g‘li Yusupov; Bekzod Xasan o‘g‘li Nurmatov; Gulnoza Yerkin qizi Imankulova; Karimov (Science and Education, 2025)
In an era increasingly shaped by technological advancements, education has undergone a profound transformation. Beyond traditional classroom settings, e-learning (electronic learning) has emerged as a pervasive and powerful modality, fundamentally altering how knowledge is disseminated and acquired. Understanding its underlying theoretical frameworks and effective methodological approaches is crucial for harnessing its full potential and ensuring a high-quality digital learning experience.